Introdutory plant biology - Kingsley R Stern (WCB, 1997)
The book includes a relatively conventional sequence of botanical subjects: structure and function; meiosis and genetics; plant biotechnology; evolution; a five-kingdom system of classification; phylogenetic sequence, the diversity of organisms traditionally regarded as plants. The book also deals with ethnobotanical aspects and information of general interest pertaining to sixteen major families of flowering plants. Finally, it gives an overview of the vast topic of ecology